Implementasi Peraturan Menteri Agama No 20 Tahun 2019 Pasal 5 Ayat (3) Tentang Pemeriksaan Dokumen Pencatatan Perkawinan di KUA Margaasih - Ibtihal Khalda; Ramdan Fawzi; Yandi Maryandi (UNISBA Press, 2023)
Abstract. In the Marriage Registration section, further document inspection is regulated in Article 5 paragraph (3)